Donors : curious connections in donor conception - Nordqvist, Petra; Gilman, Leah (Emerald studies in reproduction, culture and society, 2022)
What is expected of 21st Century egg and sperm donors, and how does being a donor impact on men's and women's own personal lives and relationships? How do donors navigate connections and relationships created by donation? What do these connections mean to them, and to the people around them--their partners, parents, siblings and children? Donor conception is becoming increasingly widespread and since the new millennium, we have witnessed a dramatic shift in the way that donor conception is regulated and practiced in many jurisdictions around the world. In the past, donor conception has often been a family secret and donors were, almost by definition, anonymous. Now, 'openness' is seen as the ideal and donors can expect to be traced or contacted by those born from their donations. But what does this shift mean for donors, and their families? This path-breaking book draws on in-depth interviews with donors, their kin and fertility counsellors, and addresses these questions by analysing how understandings of donation are shaped by the regulatory, cultural and relational contexts in which they are formed. The authors also discuss what donation stories can tell us about contemporary understandings of connectedness, time and morality in the context of reproduction and family life, and consider how reproductive 'openness' might be done differently.